Surface induced collapse of A beta(1-42) with the F19A replacement following adsorption on a single walled carbon nanotube - Jana, Asis K.; Sengupta, Neelanjana (Biophysical Chemistry, 2013)
Spontaneous adsorption of the A beta peptide on the surface of a single-walled carbon nanotube, resulting in the prevention of its intrinsic propensity to form collapsed states, could be a plausible means to hinder the peptide's initial nucleation and self-assembly. We report here the effects of sharply reducing both aromatic and hydrophobic character within the peptide's central hydrophobic core on its free and surface behavior. In such an altered peptide, complete surface adsorption is found to induce, rather than prevent, the adsorbed peptide's collapse. The weakened surface interactions of the central hydrophobic core allow its greater translational mobility on the surface, thereby facilitating interactions that lead to compaction. Both the adsorption and the subsequent collapse are accompanied by a loss of surface hydration in the modified peptide. We further find that such a two-step dewetting leads to hydration levels comparable to that obtained after compaction of the free peptide. These insights may be leveraged for designing molecular surfaces for disrupting intrinsic A beta behavior. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Amyloid beta peptide; carbon nanotube; Lateral mobility; molecular dynamics simulation; Surface induced collapse

Structural and dynamics studies of the TetR family protein, CprB from Streptomyces coelicolor in complex with its biological operator sequence - Bhukya, Hussain; Jana, Asis K.; Sengupta, Neelanjana; Anand, Ruchi (Journal of Structural Biology, 2017)
In Streptomycetes, tetracycline repressor family of transcription regulators (TetR-FTRs) controls various biological processes including antibiotic biosynthesis, cellular morphology and innate resistance. Here, we focus on understanding the structural basis of transcription regulation by CprB, a member of TetR-FTRs from S. coelicolor. CprB is implicated as a receptor of gamma-butyrolactones, a class of quorum sensing molecules, responsible for initiating secondary metabolic pathways. In order to understand the molecular mechanism of DNA recognition, the X-ray structure of CprB in complex with its biological relevant operator sequence was solved to a resolution of 3.95 angstrom. Furthermore, to refine and compliment the results, atomistic molecular dynamics simulations were carried out using the X-ray structure as the template. The studies reveal that CprB binds to DNA as dimer of dimers with this mode of interaction results in minimal distortion in the DNA, enabling these proteins to recognize multiple sequences with varying affinity. Another crucial finding from our simulation results was that the positively charged N-terminal arm of CprB brings extra stability to the protein-DNA complex by interacting with the minor-groove of the DNA and anchoring itself to the phosphate backbone. Corroborating electrophoretic mobility shift assay and fluorescence anisotropy experiments showed that the mutant AN6-CprB exhibited about 7-8 fold reduced DNA binding. Comparison with other TetR-FTRs reveals that this strategy is also employed by over 25% of TetR-FTRs, where N-terminal anchoring mechanism is used to enhance selectivity for a particular DNA sequence. (C) 2017 Elsevier Inc. All rights reserved.